Batch and Continuous Lactic Acid Production from Cassava by Streptococcus bovis - Razi, Fachrul; Yuwono, S D (Jurnal Rekayasa Kimia & Lingkungan, 2006)
Process variables were optimized for the production of lactic acid from cassava by Streptococcus bovis for batch and continuous fermentations. In the batch fermentation, maximum yield 82.5% and maximum lactic acid productivity 2.43 was achieved at 39 oC, pH 5.5 with 50 g/l cassava concentration. In the continuous fermentation maximum productivity lactic acid 1.25 g/l.h was obtained at dilution rate 0.05 /h.